Can We Uncouple Neighborhood Disadvantage and Delinquent Behaviors? An Experimental Test of Family Resilience Guided by the Social Disorganization Theory of Delinquent Behaviors. Issue 4 (19th February 2020) - Lei, Man‐Kit; Beach, Steven R. H.
Abstract : Although the influence of neighborhood disadvantage on youth development of delinquent behavior is well established, findings from this research have yet to inform the development of family‐centered prevention programming to protect youth from these erosive effects. The current paper examines the role of family integration in buffering the impact of social disadvantage in a sample of N  = 298 families randomly assigned either to a control condition or to a family‐based prevention program previously shown to enhance marriage and parenting. We first confirmed that neighborhood concentrated disadvantage predicted change in delinquent behaviors across the course of the study. Additionally, replicating prior work, parents participating in the Protecting Strong African American Families (ProSAAF) program, relative to those randomly assigned to the control group, significantly improved their use of effective communication strategies with each other and reduced ineffective conflict in front of youth. This resulted in a significant indirect effect of ProSAAF on change in youth delinquent behaviors. Furthermore, using mediated moderation analysis, the study tested the buffering effect of greater family integration, showing that experimentally produced change in interparental communication skills and the resulting reduction in youth exposure to parental conflict buffered the effect of neighborhood disadvantage on change in youth delinquent behaviors, supporting a mediated moderation model in which family environments buffer neighborhood effects. Resumen: Aunque la influencia de los barrios desfavorecidos en el desarrollo de conductas delictivas en los jóvenes está firmemente consolidada, los hallazgos de esta investigación contribuirán al desarrollo de un programa de prevención centrado en la familia para proteger a los jóvenes de estos efectos erosivos. El presente artículo analiza el papel de la integración familiar en la moderación del efecto de las desventajas sociales en una muestra de N = 298 familias asignadas aleatoriamente a una condición de control o a un programa de prevención basado en la familia que anteriormente ha demostrado mejorar el matrimonio y la crianza. Primero confirmamos que la desventaja concentrada de los barrios predijo el cambio de conductas delictivas a lo largo del transcurso del estudio. Además, replicando trabajos anteriores, los padres que participaron en el programa "Protección de Familias Afroamericanas Fuertes" (Protecting Strong African American Families, ProSAAF), en comparación con aquellos asignados aleatoriamente al grupo de control, mejoraron considerablemente su uso de estrategias de comunicación eficaz entre ellos y redujeron el conflicto ineficaz en frente de los jóvenes. Esto resultó en un efecto indirecto considerable del ProSAAF en el cambio de las conductas delictivas en los jóvenes. Además, mediante el uso del análisis de moderación mediada, el estudio evaluó el efecto moderador de una mayor integración familiar, lo cual demostró que el cambio producido experimentalmente en las habilidades de comunicación interparental y la reducción resultante de la exposición de los jóvenes al conflicto parental moderaron el efecto de la desventaja del barrio en el cambio de las conductas delictivas de los jóvenes. Todo esto respaldó un modelo de moderación mediada en el cual los entornos familiares moderan los efectos del barrio. 摘要: 虽然已有研究较好地证实了青少年所处的不利的生活社区对青少年发展过程中的犯罪行为发展有消极影响，但这些研究的结果尚未为制定以家庭为中心的预防方案提供信息，以保护青少年免受这些腐蚀性的影响。本文调查了整合家庭在缓冲社会不利条件影响方面所起的作用。本研究涉及的家庭样本有298个，从中随机分配到控制条件组或分配到基于家庭的预防方案中，此预防方案以前被证实有益于加强婚姻关系和育儿行为。我们的结果首先证实了集中在社区方面的劣势预测了在整个研究过程中青少年犯罪行为的变化。此外，与随机分配到对照组的父母相比，复制先前的研究，那些参与ProSAAF计划即参与保护强大的非裔美国人家庭的父母，显著改善了对有效沟通的使用的相互关系战略，减少青年面对的无效冲突。这就产生了ProSAAF对青少年犯罪行为变化产生的重大间接影响。该研究还利用中介调节分析，测试了家庭整合程度的缓冲效应，表明靠实验设计产生的父母间沟通技能的变化，以及由此减少青少年面对父母之间的冲突的可能性，缓冲了不利的生活社区对青少年不良行为变化的影响，支持了家庭环境缓冲社区效应的中介调节模型。